PERANAN SOSIOLINGUISTIK DALAM PENGAJARAN BAHASA: SEBUAH KAJIAN TEORETIS DAN PENERAPANNYA (TEMUAN LINGUISTIK UNTUK PENGAJARAN BAHASA) - Dwi Setiyadi (Universitas PGRI Madiun, 2012)
Language and the speech society can not even be separated to each other, because when there is a language, there will be a speech community and vice-versa. Langauge has even become one of condition of society. The existence and use of the language in society is learned through sociolinguistics, which views language as a means of communication rather than a system alone, bearing varieties in line with the given social domains. On the other hand, the traditional language teaching has regarded language as a system, which entails structuralism models of teaching. In the development of the language teaching methods, language is not merely seen as a system, rather than a communication tool, just as sociolinguistics have suggested. This articles discusses the role of sociolingusitics in the development of teaching models, beginning from the nature of speech community, language function up to sociolinguistics-based language teaching models.